Semiconducting properties of Ge-doped BaSnO3 ceramic - Koferstein, Roberto; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2010)
The electrical and optical properties of Ge-doped BaSnO3 ceramics sintered at various temperatures have been investigated to determine their semiconductor behavior. The electrical conductivity of Gedoped BaSnO3 samples increases with increase in temperature, confirming that the samples exhibit a semiconductor behavior. A maximum conductivity value of 6.31 x 10(-9) S/cm was observed for the sample sintered at 1200 degrees C. The optical band gaps of the Ge-doped BaSnO3 samples were determined by means of reflectance spectra. The variation of optical band gap with temperature was analyzed using E-g(T)= E-go + beta T relation. The rate of change of the band gap beta of BaSn0.99Ge0.01O3 was found to be 7.6 x 10(-4) (eV/degrees C). A minimum optical band gap value of 2.95 eV was observed for the sample sintered at 1400 degrees C. It is evaluated that BaSn0.99Ge0.01O3 is a wide band gap semiconductor and its semiconducting properties change with sintering temperature. (c) 2010 Elsevier B.V. All rights reserved.
Keywords: Electrical conductivity; Optical properties; Sintering; Perovskite